(untitled) (Research, Society and Development, 2021)
The violence practiced against the elderly grows disproportionately and is part of the family life. This is because it happens in a masked way, through blood ties, triggering physical, psychological and social changes. This study was developed with the aim of analyzing, through a literature review, the main violence against the elderly in the family environment. It is an integrative review, carried out in the Scientific Eletronic Library Online (SciELO), Virtual Health Library (VHL) and Google Scholar databases. 63 published articles were searched, between the years 2015 to 2020 that analyzed cases that occurred in São Luis-MA. After rigorous selection based on the inclusion criteria, only 10 articles were analyzed. During the research it was found that the violence suffered by the elderly in the family environment in São Luis-MA was categorized into types of aggression and reasons for the aggression. It was concluded with this work that there is a lack on this subject considering the need for more comprehensive interventions, essential aspects to organize and ponder public policies for the protection and valorization of the elderly.